Production and biochemical characterization of xylanases synthesized by the thermophilic fungus Rasamsonia emersonii S10 by solid-state cultivation - Zanoni, Jéssica De Araujo; Oliveira, Isabela Brunozi De; Perrone, Olavo Micali; Ortega, Julieth Ordunã; Boscolo, Maurício; Gomes, Eleni; Bonilla-Rodriguez, Gustavo Orlando (Ecletica Quimica, 2021)
The xylanolytic enzyme complex hydrolyzes xylan, and these enzymes have various industrial applications. The goal of this work was to characterize the endoxylanases produced by the thermophilic fungus Rasamsonia emersonii in solid-state cultivation. Tests were carried out to evaluate the effects of pH, temperature, glycerol and phenolic compounds on enzyme activity. Thermal denaturation of one isolated enzyme was evaluated. The crude extract from R. emersonii was applied to breakdown pretreated sugarcane bagasse, by quantifying the release of xylose and glucose. The optimum pH value for the crude enzymatic extract was 5.5, and 80 °C was the optimum temperature. Regarding the stability of the crude extract, the highest values occurred between the pH ranges from 4 to 5.5. Several phenolic compounds were tested, showing an increase in enzymatic activity on the crude extract, except for tannic acid. Zymography displayed four corresponding endoxylanase bands, which were isolated by extraction from a polyacrylamide gel. The thermodynamic parameters of isolated Xylanase C were evaluated, showing a half-life greater than 6 h at 80 °C (optimum temperature), in addition to high melting temperature (93.3 °C) and structural resistance to thermal denaturation. Pretreated sugarcane bagasse breakdown by the crude enzymatic extract from R. emersonii has good hemicellulose conversion to xylose.
Keywords: Endoxylanases; Solid-state cultivation; Sugarcane bagasse; Thermophilic fungus; Thermostability